A Comparative Study of Consumer and B2B Goods Importers' Trust and Commitment: Evidence from an Asian Developing Country. Issue 2 (May 2013) - Saleh, M. Abu; Ali, M. Yunus; Quazi, Ali
This paper develops and empirically tests a theoretical model integrating the predictors and consequences of relationship trust and commitment behaviour concerning consumer and B2B goods importers in an Asian developing market setting. A sample of 93 B2B and 139 consumer goods importers is used to test the model employing structural equation modelling. The results provide clear evidence that transaction-specific investment, environmental volatility and communication have varying impacts on trust and commitment and thus affecting international buyers' relationships and their international exchange operations. The findings broaden and deepen our understanding of how consumer and B2B goods international exchange partners' varying relationship outcomes can help reinforce their international relationships with foreign suppliers. These findings have strategic implications for maintaining effective relationships between B2B and consumer goods importers which are highlighted in this paper.